The course reflection project : faculty reflections on teaching service-learning - Schonemann, Nicole; Metzgar, Emily; Libby, Andrew (Emerald Publishing Limited : Information Age Publishing, 2015)
Service-learning is entering a post-initiatory phase. At tertiary institutions of all types and sizes, service-learning programs are common and service-learning requirements for graduation are growing in popularity. Taken together -- alongside continued faculty interest in effective teaching -- these factors have raised the visibility and popularity of service-learning. Now the greater need in service-learning is not to prove the need for, or efficacy of, service-learning, but to turn the focus squarely back on practice. Following established best practice is not enough; instructors also need to reflect on how this fits within the specific context and application of each unique course and service-learning partnership. While there are many excellent resources that detail best practice and showcase exemplary service-learning courses, faculty reflection and course revision often goes unmentioned. In response to the lack of attention on the role of reflection and course revision, we convened groups of faculty from a variety of disciplines to reflect deeply on their courses, paying specific attention to obstacles and challenges. These conversations were converted to articles for this edited collection, each chapter representing the process of reflection and revision and serving as a guide to develop effective practice in varied curricular contexts.This text contributes to the body of literature on service-learning in a unique and practical manner. Faculty teaching or interested in teaching service-learning classes would benefit from this text as well as university administrators and community service directors involved in service-learning at a programmatic and institutional level. This book should be marketed to faculty teaching disciplinary service-learning classes and service-learning pedagogy classes and administrative offices involved in service-learning. This could be a supplementary text for graduate-level pedagogy courses. Higher education institutional libraries would benefit from this text, as well as the national and state campus compact offices.
Keywords: Service learning -- Study and teaching.; Education -- Teaching -- General.; Teacher training.; Teaching skills and techniques.; elektronické knihy; electronic books